2022
DOI: 10.3390/ijms23031352
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Molecular Mechanisms of Renal Hepcidin Induction and Protection upon Hemoglobin-Induced Acute Kidney Injury

Abstract: Hemolysis is known to cause acute kidney injury (AKI). The iron regulatory hormone hepcidin, produced by renal distal tubules, is suggested to exert a renoprotective role during this pathology. We aimed to elucidate the molecular mechanisms of renal hepcidin synthesis and its protection against hemoglobin-induced AKI. In contrast to known hepatic hepcidin induction, incubation of mouse cortical collecting duct (mCCDcl1) cells with IL-6 or LPS did not induce Hamp1 mRNA expression, whereas iron (FeS) and hemin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…In recent work, we demonstrated that proximal tubular FtH deletion exacerbates AKI and leads to significant mortality during rhabdomyolysis (16). These studies were corroborated by the use of iron chelators and inducers of heme oxygenase expression within the kidney (10,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 65%
“…In recent work, we demonstrated that proximal tubular FtH deletion exacerbates AKI and leads to significant mortality during rhabdomyolysis (16). These studies were corroborated by the use of iron chelators and inducers of heme oxygenase expression within the kidney (10,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 65%
“…Hepcidin expression increases under iron overload and inflammation and reduces under iron deficiency and hypoxia [ 186 ]. However, many of the current studies on hepcidin and inflammation are in the hepatocytes or AKI [ 187–189 ]. In IgAN, immune damage in the mesangial region promotes IL-6 secretion [ 171 , 190 ], and the tubular damage caused by hematuria also leads to an increase in IL-6 [ 26 , 191 ].…”
Section: The Interconnection Of Iron Metabolism Chronic Inflammation ...mentioning
confidence: 99%
“…Другим местом выработки гепсидина являются дистальные собирательные канальцы почек, где индуктором его синтеза в большей мере является повышенный уровень железа/гема, нежели ИЛ-6, что, вероятно, играет важную протективную роль при остром повреждении почек, вызванном гемолизом [14].…”
Section: патогенезunclassified